Clinical response scores to predict blood pressure and renal function improvement following renal artery stenting for atherosclerotic renal artery stenosis. (25th November 2020) - Kablak-Ziembicka, A; Roslawiecka, A; Badacz, R; Sokolowski, A; Musialek, P; Rzeznik, D; Legutko, J; Zmudka, K; Przewlocki, T
Abstract: Background: It is little known about predictors of systolic (SBP) and diastolic (DBP) blood pressure or renal function (eGFR) improvement in patients with atherosclerotic renal artery stenosis (ARAS) undergoing stent-assisted angioplasty (PTA). Therefore, we aimed to build a prediction scores that would indicate characteristics of patient subsets with ARAS most likely to have clinical improvement following PTA. Methods: 201 patients who underwent PTA for ARAS (2003–2018) were categorized as eGFR or SBP/DBP responders based on eGFR increase of ≥11 ml/min/1.73m 2, decrease of SBP ≥20mmHg and DBP ≥5mmHg at 12-months following PTA. The remaining patients were classified as non-responders. The performance of logistic regression models were evaluated by basic decision characteristics. Continuous data have been transformed into binary coding with help of operating characteristic (ROC) curve. Predictive models have been constructed for each followed by construction of predictive models in each of 3 categories. Results: Logistic regression analysis showed that: baseline SBP>145 mmHg, DBP >82 mmHg, previous myocardial infarction and Renal-Aotric-Ratio >5.1 were independent influencing factors of SBP response, with relative risk percentage shares of 69.8%; 12.1%; 10.9%; and 7.2%, respectively (sensitivity: 82%, specificity: 86.3%, positive (PPV):82% and negative (NPV) predictive values: 86.3%). The DBP decrease prediction model included baseline SBP >145 mmHg and DBP >82 mmHg, the ARAS progression, index kidney length >106 mm, and bilateral PTA with respective shares of 35.0%; 21.8%; 18.2%; 13.3% and 11.8%. (sensitivity: 76%, specificity: 77.8%, PPV: 80.7% and NPV: 72.6%). The eGFR increase was associated with baseline serum creatinine >122 μmol/L but eGFR greater than 30 ml/min/1.73m 2, index kidney length >98 mm, end-diastolic velocity in index renal artery, renal resistive index <0.74, and requirement for >3 BP medications, with respective shares of 24.4%; 24.4%; 21.2%; 15% and 15% (sensitivity: 33.3%, specificity: 93.5%, PPV: 65.6% and NPV: 78.9%). Conclusions: Current study identified clinical characteristics of patients who most likely to respond to PTA for ARAS. The sutability of the score should be verified in a prospective cohort of patients referred to PTA of ARAS Funding Acknowledgement: Type of funding source: None